Respiratory virome profiles reflect antiviral immune responses. Issue 5 (17th January 2023) - Rovira Rubió, Judit; Megremis, Spyridon; Pasioti, Maria; Lakoumentas, John; Constantinides, Bede; Xepapadaki, Paraskevi; Bachert, Claus; Finotto, Susetta; Jartti, Tuomas; Andreakos, Evangelos; Stanic, Barbara; Akdis, Cezmi A.; et al.
Abstract: Background: From early life, respiratory viruses are implicated in the development, exacerbation and persistence of respiratory conditions such as asthma. Complex dynamics between microbial communities and host immune responses shape immune maturation and homeostasis, influencing health outcomes. We evaluated the hypothesis that the respiratory virome is linked to systemic immune responses, using peripheral blood and nasopharyngeal swab samples from preschool‐age children in the PreDicta cohort. Methods: Peripheral blood mononuclear cells from 51 children (32 asthmatics and 19 healthy controls) participating in the 2‐year multinational PreDicta cohort were cultured with bacterial (Bacterial‐DNA, LPS) or viral (R848, Poly:IC, RV) stimuli. Supernatants were analysed by Luminex for the presence of 22 relevant cytokines. Virome composition was obtained using untargeted high throughput sequencing of nasopharyngeal samples. The metagenomic data were used for the characterization of virome profiles and the presence of key viral families (Picornaviridae, Anelloviridae, Siphoviridae). These were correlated to cytokine secretion patterns, identified through hierarchical clustering and principal component analysis. Results: High spontaneous cytokine release was associated with increased presence of Prokaryotic virome profiles and reduced presence of Eukaryotic and Anellovirus profiles. Antibacterial responses did not correlate with specific viral families or virome profile; however, low antiviral responders had more Prokaryotic and less Eukaryotic virome profiles. Anelloviruses and Anellovirus‐dominated profiles were equally distributed among immune response clusters. The presence of Picornaviridae and Siphoviridae was associated with low interferon‐λ responses. Asthma or allergy did not modify these correlations. Conclusion: Antiviral cytokine responses at a systemic level reflect the upper airway virome composition. Individuals with low innate interferon responses have higher abundance of Picornaviruses (mostly Rhinoviruses) and bacteriophages. Bacteriophages, particularly Siphoviridae, appear to be sensitive sensors of host antimicrobial capacity, while Anelloviruses are not correlated with TLR‐induced immune responses. Abstract : Respiratory virome profiles of preschool children were associated with spontaneous cytokine release and stimulated antiviral responses from PBMCs, independent of asthma/allergy status. Prokaryotic (bacteriophage)‐type viromes dominated the high spontaneous cytokine release responder cluster. High antiviral responders included more eukaryotic‐dominated profiles, while low interferon lambda release correlated with increased presence of Picornaviridae and Siphoviridae.Abbreviations: Bact‐DNA, endotoxin‐free bacterial DNA; LPS, lipopolysaccharides from E. coli 0111:B4; NGS, next generation sequencing; PBMCs, peripheral blood mononuclear cells; Poly I:C, polyinosinic–polycytidylic acid potassium salt; R848, resiquimod; RV‐A, rhinovirus A